(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Assess some risk indicatiors to the health of people in Hanoi due to Aflatoxin B1 contamination foods. Research objects and methods: Cross-sectional descriptive study with analysis. The research subjects are rice, corn, peanuts and sesame samples in Dong Da district and Quoc Oai district, Hanoi, collected from January 2022 to March 2023. Results: Study results showed that the estimated daily intake (EDI) of Aflatoxin B1 in collected cereal samples ranged from 4.8-8.1; 4.3-7.0; 2.8-4.5 and 2.8-4.5 ng/kg body weight/day for age groups 3-6 years old, 7-11 years old, 12-18 years old and over 18 years old, respectively. The HQ values for all age groups > 1; however, the HI values were < 1. The estimated average risk of liver cancer is 0.1664-0.2820; 0.1481-0.2425; 0.0969-0.1579 and 0.0978-0.1560 cases/year/100,000 people for age groups 3-6 years old, 7-11 years old, 12-18 years old and over 18 years old, respectively. Conclusion: Although the overall health risks from dietary exposure to Aflatoxin B1 is low, bad influence for health can occur, especially when consumed during long periods of time.